Trans-thoracic versus retropleural approach for symptomatic thoracic disc herniations: comparative analysis of 94 consecutive cases. (4th March 2021) - Soda, Christian; Faccioli, Franco; Marchesini, Nicolò; Ricci, Umberto M.; Brollo, Marco; Annicchiarico, Luciano; Benato, Cristiano; Tomasi, Ivan; Pinna, Giampietro P.; Teli, Marco
Abstract: Purpose: The authors illustrate their results in the surgical treatment of symptomatic thoracic disc herniations (TDHs) by comparing the traditional open to the less invasive retropleural lateral approaches. Methods: Retrospective review of 94 consecutive cases treated at a single Institution between 1988 and 2014. Fifty-two patients were males, 42 females, mean age was 53.9 years. Mean follow-up was 46.9 months (12–79 months). 33 patients were diagnosed with a giant thoracic disc herniation (GTDH). Upon admission, the most common symptoms were: motor impairment (91.4%, n = 86), neuropathic radicular pain with VAS > 4 (50%), bladder and bowel dysfunction (57.4% and 41.4% respectively) and sensory disturbances (29.7%). The surgical approach was based upon level, laterality and presence or absence of calcified lesions. Results: Decompression was performed in 7 cases via a thoraco-laparo-phrenotomy and in 87 cases via an antero-lateral thoracotomy. Out of the latter cases, 49 (56%) were trans-thoracic trans-pleural approaches (TTA) and 38 (44%) were less invasive retropleural approaches (MIRA). At follow-up, there were 59.5% neurologically intact patients according to the McCormick Scale, while 64.8% and 67% had no bladder or bowel dysfunction respectively. Complications occurred in 24 patients (25.5%). Pulmonary complications were the commonest (12.7%) with pleural effusion being significantly more common in patients treated with TTA compared to MIRA (20% vs 5.2%: X 2 4.13 P:0.042). Severe post-operative neuralgia (VAS 7–10) was also significantly more frequent in the TTA group (22.4% vs 2.6% X 2 7.07 p 0.0078). Conclusions: MIRA is a safe and effective technique to obtain adequate TDH decompression and is associated with lower morbidity compared to TTA.